Effect of methionine and trace minerals (zinc, copper and manganese) supplementation on growth performance of broilers subjected to Eimeria challenge - Chen, J.; Yan, F.; Kuttappan, V.A.; Cook, K.; Buresh, B.; Roux, M.; Hancock, D.; Vázquez-Añón, Mercedes (Frontiers in Physiology, 2022)
Coccidiosis is a major intestinal challenge that causes economic loss to the broiler industry. Two battery cage studies were conducted to evaluate the effect of trace minerals, source and dose of methionine on growth performance and gut health of broilers subjected to Eimeria challenge. Study#1 consisted of 9 -treatments of 2x2x2 factorial design + 1 arrangement with main factors of methionine (Met) sources (DL-Met vs 2-hydroxy-4-(methylthio)-butanoic acid (HMTBa)), total sulfur amino acid (TSAA) levels (high vs low; ±5% of recommended level), and sources of trace minerals (TM) Zn:Cu:Mn in the form of sulfates (80:20:100ppm) vs mineral methionine hydroxy-analogue bis-chelate (MMHAC, MINTREX®Zn:Cu:Mn, 40:10:50ppm), each with 8 pens of 10 birds. Study#2 consisted of 2 treatments - ITM [ZnSO4:tribasic copper chloride (TBCC):MnSO4 110:125:120ppm] and MMHAC (Zn:Cu:Mn, 40:30:40ppm), each with 36 pens of 7 birds. All birds except for treatment 9 in study#1 were orally gavaged with 1x, 4x and 16x recommended dose of coccidiosis vaccine on d0, d7 and d14, respectively. Data were subjected to one-way and/or three-way ANOVA, and means were separated by Fisher’s protected LSD test with significance at P<0.05. In study#1, factorial analysis revealed the main effects of TSAA level and TM, but not Met source. High TSAA level improved body weight and cumulative feed intake at 14, 20, and 27d. MMHAC improved body weight at 14, and 27d; feed intake at 14, 20, and 27d; and cumulative FCR at 27d vs sulfates. One-way ANOVA analysis showed that birds fed MMHAC and high levels of TSAA regardless of Met source had similar body weight as unchallenged birds on d27. In study#2, MMHAC improved body weight and cumulative FCR, and reduced jejunal IL17 gene expression on d28. In summary, in broilers subjected to Eimeria challenge, supplementation of the reduced levels of bis-chelated trace minerals MMHAC improved growth performance compared to high levels of ITM (sulfates or TBCC), which might partially result from better immune response, high levels of TSAA improved growth performance, Met source had no effect. Supplementation of both bis-chelated trace minerals MMHAC and high levels of TSAA could overcome the growth performance challenge issue due to coccidiosis.